2008
DOI: 10.1021/jm8007486
|View full text |Cite
|
Sign up to set email alerts
|

Gedunin, a Novel Hsp90 Inhibitor: Semisynthesis of Derivatives and Preliminary Structure−Activity Relationships

Abstract: Gedunin (1), a tetranortriterpenoid isolated from the Indian neem tree (Azadirachta indica), was recently shown to manifest anticancer activity via inhibition of the 90 kDa heat shock protein (Hsp90) folding machinery and to induce the degradation of Hsp90-dependent client proteins similar to other Hsp90 inhibitors. The mechanism of action by which gedunin induces client protein degradation remains undetermined, however, prior studies have demonstrated that it does not bind competitively versus ATP. In an effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 20 publications
2
113
0
1
Order By: Relevance
“…However, we saw no direct molecular effect on L54R GFP-dystrophin levels at tolerated concentrations up to 50 μM. Finally, we tested gedunin, which binds to and inhibits Hsp90, thereby releasing bound HSF1 for transcriptional activity (38,39). Increasing L54R GFP-dystrophin was observed in cells treated with 10-80 μM gedunin, suggesting that pharmacologic activation of the heat shock system can facilitate stabilization of mutant dystrophin.…”
Section: L54r and L172h Mutant Dystrophins Are Degraded By The Proteamentioning
confidence: 82%
“…However, we saw no direct molecular effect on L54R GFP-dystrophin levels at tolerated concentrations up to 50 μM. Finally, we tested gedunin, which binds to and inhibits Hsp90, thereby releasing bound HSF1 for transcriptional activity (38,39). Increasing L54R GFP-dystrophin was observed in cells treated with 10-80 μM gedunin, suggesting that pharmacologic activation of the heat shock system can facilitate stabilization of mutant dystrophin.…”
Section: L54r and L172h Mutant Dystrophins Are Degraded By The Proteamentioning
confidence: 82%
“…Gedunin failed to compete with geldanamycin in a fluorescence polarization assay using purified Hsp90, but it showed a synergistic effect with 17-AAG 2 in inhibiting growth of LNCaP cells and AR signaling (23). Extensive chemical modification of gedunin led to the conclusion that Michael acceptor properties of gedunin are not required for its inhibitory activity, and consequently, gedunin represents a promising scaffold for further development (25), and its molecular mechanism of action needs further characterization.…”
mentioning
confidence: 99%
“…Chemical structure of gedunin was obtained from PubChem chemistry database, which has been reported to inhibit Hsp90 protein [8]. The structure of the compound was then drawn in ChemSketch software 11.02 (Advanced Chemistry Development, Inc. ACD/Labs) and 3-D structure optimization was done by adding hydrogen atoms to the ligand.…”
Section: Preparation Of Ligandmentioning
confidence: 99%
“…The dependence of several oncogenes and other signaling processes involved in cancer progression on Hsp90 makes it a potential target against cancers [6,7]. It was shown that gedunin as an anticancer agent inhibits the function of Hsp90 protein, resulting in the degradation and improper functioning of the client proteins, similar to other Hsp90 inhibitors [8]. Numerous Hsp90 inhibitors, identified as anticancer agents such as radicicol, geldanamycin (GA), and GA derivatives, block Hsp90 activity by binding to the N-terminal ATP pocket of the protein and inhibiting ATPase activity [9].…”
Section: Introductionmentioning
confidence: 99%